A study of evaluation of unhealthy cervix by various diagnostic modalities - Gohil, Ami M.; Ponde, Sanjay; Agrawal, Poorvi; Bal, Himadri (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: This study was carried out to evaluate cases of unhealthy cervix by using Pap (Papanicolaou) smear, colposcopy and cervical biopsy and to arrive at a definitive diagnosis. It correlated the findings of Pap smear, colposcopy and histopathology. It is important to strictly implement the screening program and spread awareness of the disease symptoms and its management to reduce the overall incidence of morbidity and mortality reported due to cervical cancer. Methods: A total 120 patients satisfying the inclusion/exclusion criteria were recruited for the study and informed consent was taken from all the participants. Pap smear was taken for all the cases. Then cases were subjected to colposcopy followed by biopsy. All the findings were correlated and analyzed. The findings of Pap smear and colposcopy were correlated with the gold standard of histopathology. Results: The sensitivity and specificity of Pap smear and colposcopy with respect to cervical biopsy were 53.1% and 98.7%, 87.87% and 72.72% respectively. Colposcopy had higher sensitivity and lower specificity than Pap smear for screening of cancer cervix. Conclusions: Cervical cancer is one of the preventable and highly curable conditions when diagnosed in the precancerous stage. The incidence of deaths resulting from cervical cancer can be brought down with adequate cervical cancer screening. Colposcopy and colposcopy directed biopsy should be done along with Pap smear in screening for early detection of cervical cancer since the accuracy of detection of cervical abnormalities is higher when these two methods are used complementarily.